PHASE STAGES OF CULTURE SHOCK DEPICTED IN THE PICTURE BOOK YOON SERIES - Wulan, Kurnia; Marwinda, Kristin (Universitas 17 Agustus 1945 Semarang, 2024)
The writer analyzes three picture books from the Yoon series by Helen Recorvits andGabi Swiatkowska titled